Cross-Border Interbank Networks, Banking Risk and Contagion - Lena Tonzer (FIW - Research Centre International Economics, 2013)
Recent events emphasize the role of cross-border linkages between banking systems in transmitting local developments across national borders. This paper analyzes whether international linkages in interbank markets affect the stability of interconnected banking systems and channel financial distress within a network consisting of banking systems of main advanced countries for the period 1993-2009. Methodologically, I use a spatial modelling approach to test for spillovers in cross-border interbank markets. The results suggest that foreign exposures in banking play a significant role in channelling banking risk: I find that countries which are linked through foreign borrowing or lending positions to more stable banking systems abroad are significantly affected by positive spillover effects. From a policy point of view, this implies that especially in stable times linkages in the banking system can be beneficial, while they have to be taken with caution in times of financial turmoil covering the whole system.
Keywords: F21; F34; F65; G21; O16; 330; Financial contagion; financial integration; banking networks